Implementation of Islamic Religious Education in Building Religious Values of Students at SMP Muhammadiyah 3 Bandung - Muchtarom, Muchtarom (The International Journal of Education Management and Sociology, 2024)
This study employs a qualitative descriptive approach, focusing on field research. Data were gathered through observation, interviews, and documentation, utilizing purposive sampling and snowball techniques. Descriptive analysis was used to interpret the data. The findings indicate that Islamic religious education at SMP Muhammadiyah 3 Bandung is implemented effectively and thoroughly. Religious values are integrated into daily activities, including greetings, handshakes, polite speech, courteous behavior, and mutual respect among teachers and peers. The religious curriculum includes programs such as TPA, congregational dhuha and dhuhur prayers, and activities like tahfid, speeches, cultum, lectures, studies, infaq, and memorization of selected Qur'anic verses. Exemplary behavior and discipline are consistently promoted by all school members. Intracurricular Islamic religious education follows the 2013 curriculum, emphasizing student-centered learning and contextual examples. The practice of religious values is assessed through attitude evaluations, monitoring of attitude development, and religious practices.